2019
DOI: 10.1016/j.molp.2019.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Phytophthora sojae Effector PsAvh240 Inhibits Host Aspartic Protease Secretion to Promote Infection

Abstract: Plants secrete defense molecules into the extracellular space (the apoplast) to combat attacking microbes. However, the mechanisms by which successful pathogens subvert plant apoplastic immunity remain poorly understood. In this study, we show that PsAvh240, a membrane-localized effector of the soybean pathogen Phytophthora sojae, promotes P. sojae infection in soybean hairy roots. We found that PsAvh240 interacts with the soybean-resistant aspartic protease GmAP1 in planta and suppresses the secretion of GmAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 47 publications
0
41
0
1
Order By: Relevance
“…WY motifs are the most prominent C‐terminal motifs conserved across the oomycete RxLR superfamily (Jiang et al ., ). Protein structural analysis of several RxLR effectors revealed that the WY motif fold serves as a chassis for the evolution of novel functions in oomycete effectors, while maintaining their structural integrity (Boutemy et al ., ; Chou et al ., ; Leonelli et al ., ; Maqbool et al ., ; Zhao et al ., ; Guo et al ., ). Our analysis showed that mutation of the WY domain did not affect the transcript level of PSR1 , but markedly decreased its protein level, suggesting that an intact WY domain is important for the protein stability/accumulation of PSR1.…”
Section: Discussionmentioning
confidence: 97%
“…WY motifs are the most prominent C‐terminal motifs conserved across the oomycete RxLR superfamily (Jiang et al ., ). Protein structural analysis of several RxLR effectors revealed that the WY motif fold serves as a chassis for the evolution of novel functions in oomycete effectors, while maintaining their structural integrity (Boutemy et al ., ; Chou et al ., ; Leonelli et al ., ; Maqbool et al ., ; Zhao et al ., ; Guo et al ., ). Our analysis showed that mutation of the WY domain did not affect the transcript level of PSR1 , but markedly decreased its protein level, suggesting that an intact WY domain is important for the protein stability/accumulation of PSR1.…”
Section: Discussionmentioning
confidence: 97%
“…With deepening studies of functional genomics, proteomics, computer-aided design, and X-ray crystallography, many new potential molecular targets of pesticides have been identified and structurally characterized. In particular, in plant pathology, the structures of Phytophthora effectors PexRD54 and PexRD52, VR3a11 [ 89 , 90 ], and Avh240 [ 91 ] were solved, and the complex crystal structures of the Magnaporthe oryzae immune receptors RGA5A_S and RGA5A_S–AVR1-CO39 were solved [ 92 , 93 ], which aided in investigating the molecular mechanisms used by the rice disease-resistant protein RGA5 to recognize effectors. These structures provide a basis for studying the mutation-related mechanisms of effectors and provide important data for functional research and fungicide discovery.…”
Section: Discussionmentioning
confidence: 99%
“…Nudix水解酶活性降解ADPR, NADH等信号分子, 进而 抑制植物免疫 [216] , 其活性依赖于植物亲环素 [218] , 揭示 了病原蛋白利用宿主因子加工进而发挥毒性功能的新 机制; 发现Avh262通过稳定植物内质网蛋白BiP, 缓解 内质网压力引起的细胞坏死, 从而促进大豆疫霉侵 染 [219] ; 发现效应蛋白Avh23和Avh52通过调控寄主染 色质组蛋白的乙酰化修饰, 进而精确地抑制抗病基因 表达, 促进感病基因的表达, 从而在表观修饰水平有 效地干扰植物免疫反应的机制 [220,222] ; 与中国科学院 上海植物逆境中心研究组合作, 解析了大豆疫霉效应 蛋白Avh240的晶体结构, 并鉴定到了一个植物胞外免 疫的新成员GmAP1, 揭示了大豆疫霉菌抑制GmAP1 外泌的这一干扰植物胞外免疫的新机制 [223] ; 发现了疫…”
Section: 种保守表观遗传调控机制 测序鉴定出了400多个进unclassified